Еще один универсальный закон бюрократии? - Попова, И. (Социология: теория, методы, маркетинг, 2007)
Analyzing both the monitoring survey data and historical materials, the author makes an assumption that under certain circumstances, the capitalism development, determines and realizes a general algorithm of the bureaucracy's behavior. This can be regarded as one of the universal laws of the bureaucracy's functioning.